Dentifying Opportunities To Reduce The Consumption Of Energy Across Mining And Mineral Processing Plants - R. Steele (Society for Mining, Metallurgy & Exploration, 2011)
In addition to compliance with government emissions and reporting requirements, mining and mineral processing companies are increasing energy efficiency to reduce costs and become more competitive in the global marketplace. One of the major obstacles to identifying opportunities for increased energy efficiency is the lack of readily available data on energy use, and more importantly the energy use linked to production data, that identify energy reduction opportunities. As well as energy reduction, mining and mineral processing companies often struggle with the prediction of energy use, and are often penalized for under or over forecasting. Once again, it is the lack of timely information that makes this prediction difficult. This paper looks at expanding the use of a Manufacturing Execution Systems by integrating with Energy Solutions. This will provide automatic, timely information, at a granularity that makes it easier to identify energy reduction opportunities, reduce energy costs, and better predict energy use in a mining and mineral processing operation.